Morphing Process Research of UAV with PID Controller. (2015) - Haoqin, Su; Zhan, Huang; Xiaoxiang, Bao; Hongwei, Shi; Jing, Song
Abstract: Morphing UAV(Unmanned Aerial Vehicle) change its profile to adapt for wide flight condition, and attach lots of flight tasks, so PID controller is needed to satisfy the morphing requirement of UAV. Firstly this paper shows the expression of morphing aerodynamic process. Then, characteristic values of UAV are analyzed, and PID controller is brought out to satisfy stable capacity of UAV closed system. At last, simulation is run with traditional PID controller, and the best morphing time can be got from time sets.